A protocol for generating germ-free Heligmosomoides polygyrus bakeri larvae for gnotobiotic helminth infection studies - Gabriel A. Russell (Elsevier, 2021)
Summary: The microbes indigenous to helminth species are a major obstacle to deciphering host-parasite interactions. Repurposing a system of reversible bacterial colonization, we have generated germ-free Heligomosomoides polygyrus bakeri (Hpb) larvae that maintain the sterility of axenic mice upon infection. This protocol provides a valuable tool for controlled studies of helminth-microbiota-immune interactions.